Age-related arterial immune cell infiltration in mice is attenuated by caloric restriction or voluntary exercise - Trott, Daniel W (Exp Gerontol, 2016)
Age-related arterial inflammation is associated with dysfunction of the arteries and increased risk for cardiovascular disease. To determine if aging increases arterial immune cell infiltration as well as the populations of immune cells principally involved, we tested the hypothesis that large elastic and resistance arteries in old mice would exhibit increased immune cell infiltration compared to young controls. Additionally, we hypothesized that vasoprotective lifestyle interventions such as life-long caloric restriction or 8 weeks of voluntary wheel running would attenuate age-related arterial immune cell infiltration. The aorta and mesenteric vasculature with surrounding perivascular adipose was excised from young normal chow (YNC, 4–6 months, n = 10), old normal chow (ONC, 28–29 months, n = 11), old caloric restricted (OCR, 28–29 months, n = 9) and old voluntary running (OVR, 28–29 months, n = 5) mice and digested to a single cell suspension. The cells were then labeled with antibodies against CD45 (total leukocytes), CD3 (pan T cells), CD4 (T helper cells), CD8 (cytotoxic T cells), CD19 (B cells) CD11b and F4/80 (macrophages) and analyzed by flow cytometry. Total leukocytes, T cells (both CD4(+) and CD8(+) subsets), B cells and macrophages in both aorta and mesentery were all 5–6 fold greater in ONC compared to YNC. Age-related increases in T cell (both CD4(+) and CD8(+)), B cell and macrophage infiltration in aorta were abolished in OCR mice. OVR mice exhibited 50% lower aortic T cell and normalized macrophage infiltration. B cell infiltration was not effected by VR. Age-related mesenteric CD8(+) T cell and macrophage infiltration was normalized in OCR and OVR mice compared to young mice, whereas B cell infiltration was normalized by CR but not VR. Splenic CD4(+) T cells from ONC mice exhibited a 3 fold increase in gene expression for the T helper (Th)1 transcription factor, Tbet, and a 4 fold increase in FoxP3, a T regulatory cell transcription factor, compared to YNC. Splenic B cells and mesenteric macrophages from old mice exhibited decreased proinflammatory cytokine gene expression regardless of treatment group. These results demonstrate that aging is associated with infiltration of immune cells around both the large-elastic and resistance arteries and that the vasoprotective lifestyle interventions, CR and VR, can ameliorate age-related arterial immune cell infiltration.